PQBP1 regulates striatum development through balancing striatal progenitor proliferation and differentiation - Wenhua Liu; Hao Xie; Xian Liu; Shoujing Xu; Shanshan Cheng; Zheng Wang; Ting Xie; Zi Chao Zhang; Junhai Han (Cell Reports, 2023)
Summary: The balance between cell proliferation and differentiation is essential for maintaining the neural progenitor pool and brain development. Although the mechanisms underlying cell proliferation and differentiation at the transcriptional level have been studied intensively, post-transcriptional regulation of cell proliferation and differentiation remains largely unclear. Here, we show that deletion of the alternative splicing regulator PQBP1 in striatal progenitors results in defective striatal development due to impaired neurogenesis of spiny projection neurons (SPNs). Pqbp1-deficient striatal progenitors exhibit declined proliferation and increased differentiation, resulting in a reduced striatal progenitor pool. We further reveal that PQBP1 associates with components in splicing machinery. The alternative splicing profiles identify that PQBP1 promotes the exon 9 inclusion of Numb, a variant that mediates progenitor proliferation. These findings identify PQBP1 as a regulator in balancing striatal progenitor proliferation and differentiation and provide alternative insights into the pathogenic mechanisms underlying Renpenning syndrome.